Cross-linking assessment after accelerated ageing of ethylene propylene diene monomer rubber - Tomer, N. S.; Delor-Jestin, Florence; Singh, R. P.; Lacoste, Jacques (Polymer Degradation and Stability, 2007)
The ageing of filled and cross-linked ethylene propylene diene elastomer (EPDM) has been studied under accelerated UV irradiation (lambda >= 290 nm) at 60 degrees C, thermal ageing at 100 degrees C and in nitric acid vapours for different time intervals. Hardness measurements were performed. DSC-thermoporosimetry was used to estimate the mesh size distribution and cross-linking densities for each ageing. The development of functional groups was monitored by ATR spectroscopy. An increase in oxidation with exposure time after the different types of ageing was observed. The thermal stability of EPDM was assessed by TGA and evolved volatile gases were identified using FTIR spectroscopy. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ageing; EPDM; Oxidation; thermal analysis; thermoporosimetry